Exercise attenuates polyglutamine‐mediated neuromuscular degeneration in a mouse model of spinal and bulbar muscular atrophy - Tomoki Hirunagi; Hideaki Nakatsuji; Kentaro Sahashi; Mikiyasu Yamamoto; Madoka Iida; Genki Tohnai; Naohide Kondo; Shinichiro Yamada; Ayuka Murakami; Seiya Noda; Hiroaki Adachi; Gen Sobue; et al. (Wiley, 2024)
Abstract Background Spinal and bulbar muscular atrophy (SBMA) is a hereditary neuromuscular disorder caused by the expansion of trinucleotide cytosine-adenine-guanine (CAG) repeats, which encodes a polyglutamine (polyQ) tract in the androgen receptor (AR) gene. Recent evidence suggests that, in addition to motor neuron degeneration, defective skeletal muscles are also the primary contributors to the pathogenesis in SBMA. While benefits of physical exercise have been suggested in SBMA, underlying mechanism remains elusive. Methods We investigated the effect of running exercise in a transgenic mouse model of SBMA carrying human AR with 97 expanded CAGs (AR97Q). We assigned AR97Q mice to exercise and sedentary control groups, and mice in the exercise group received 1‐h forced running wheel (5 m/min) 5 days a week for 4 weeks during the early stage of the disease. Motor function (grip strength and rotarod performance) and survival of each group were analysed, and histopathological and biological features in skeletal muscles and motor neurons were evaluated. Results AR97Q mice in the exercise group showed improvement in motor function (~40% and ~50% increase in grip strength and rotarod performance, respectively, P < 0.05) and survival (median survival 23.6 vs. 16.7 weeks, P < 0.05) with amelioration of neuronal and muscular histopathology (~1.4‐fold and ~2.8‐fold increase in motor neuron and muscle fibre size, respectively, P < 0.001) compared to those in the sedentary group. Nuclear accumulation of polyQ‐expanded AR in skeletal muscles and motor neurons was suppressed in the mice with exercise compared to the sedentary mice (~50% and ~30% reduction in 1C2‐positive cells in skeletal muscles and motor neurons, respectively, P < 0.05). We found that the exercise activated 5'‐adenosine monophosphate‐activated protein kinase (AMPK) signalling and inhibited mammalian target of rapamycin pathway that regulates protein synthesis in skeletal muscles of SBMA mice. Pharmacological activation of AMPK inhibited protein synthesis and reduced polyQ‐expanded AR proteins in C2C12 muscle cells. Conclusions Our findings suggest the therapeutic potential of exercise‐induced effect via AMPK activation in SBMA.